COMMUNITY-BASED PRODUCTION OF LIQUID SMOKE AS A NON-CARCINOGENIC FISH PRESERVATIVE: - - Taufik, Muhammad; Boby Cahyady; Rossy Nurhasanah; Masruroh, Pingkan; Syahputra, Muhammad Rizky; Azzahrah, Nabilah Azka; Zul Alfian; Mariany Razali (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2025)
The growing demand for safe fish preservatives has encouraged the use of liquid smoke as an alternative to high-temperature processing, which may form carcinogenic compounds. This community service program focused on producing coconut-shell-based liquid smoke through pyrolysis followed by distillation to obtain grade-2 liquid smoke. Acetic acid content was determined using alkalimetry with 0.1 N NaOH. The results showed an increase in acetic acid concentration from 1% to 6.5%, meeting the grade-2 standard of SNI 8985:2021. Application through 20-minute immersion preserved fish quality for up to three days without generating carcinogenic properties. Beyond product development, the program strengthened local socio-economic conditions by providing training, empowering residents to produce liquid smoke independently, and opening new micro-enterprise opportunities. This demonstrates that community-based production can supply safe, standardized preservatives while enhancing economic resilience in Manunggal Village.